Adaptation and validation of the MLQ-5X leadership scale to the Spanish educational context - Moreno-Casado, Héctor; Leo-Marcos, Francisco Miguel; López-Gajardo, Miguel Ángel; García-Calvo, Tomás; Cuevas, Ricardo; Sánchez-Oliva, David (Anales de Psicología / Annals of Psychology, 2021)
Drawing from the transformational leadership theory, this study aimed to analyze the psychometric properties of a version adapted to the educational environment of the Multifactor Leadership Questionnaire (MLQ-5X). A total of 1551 Spanish students (M = 15.47 years ± 0.72; 679 boys and 872 girls) from 31 secondary schools participated in the study. The confirmatory factor analysis of the initial structure of nine factors of the scale determined the need to eliminate two items of the direction by passive exception factor, grouping passive leadership into a single factor. In a second eight-factor model, high correlations were found between the factors of transformational leadership, indicating the need to establish a first-order factor. Finally, a third model was tested that obtained adequate values ​​of validity and reliability, which was composed of 34 items distributed in 4 main factors (transformational leadership, contingent reward, leadership by active exception and passive leadership) and 5 secondary factors for transformational leadership (idealized influence behavior, attributed idealized influence, inspirational motivation, intellectual stimulation and individualized consideration). Therefore, the Spanish version of the MLQ-5X in the educational field can be used to assess the transformational leadership of teachers from the perception of the students.